2017
DOI: 10.12659/msm.899801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mild Hypercapnia on Lung Oxygenation in Sitting Position During Shoulder Arthroscopy Under General Anesthesia

Abstract: BackgroundMild hypercapnia is permitted during surgeries in sitting position under general anesthesia to maintain cerebral regional oxygen saturation (rSO2). However, since hypoventilation may cause gas exchange impairment, we evaluated effects of mild hypercapnia on lung oxygenation during shoulder arthroscopy in sitting position.Material/MethodsForty patients were randomly allocated to a normocapnia group (ETCO2 35 mmHg, n=20) or a hypercapnia group (45 mmHg, n=20). The mean arterial pressure (MAP), heart ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Cerebral oxygenation monitoring was performed using INVOS™ 5100 B/C (Medtronic, Ireland) cerebral oximetry monitoring devices [ 7 , 13 , 20 - 27 , 29 ] (near-infrared reflectance spectroscopy) in all included studies in this review, except in a single study [ 28 ] in which the FORE-SIGHT™ device (Edwards Lifesciences, USA) was used. All the studies reported baseline data with respect to rSO 2 including pre- and post-induction values, except for a single study [ 24 ] in which only the mean (SD) maximum fall of cerebral saturation values was reported.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cerebral oxygenation monitoring was performed using INVOS™ 5100 B/C (Medtronic, Ireland) cerebral oximetry monitoring devices [ 7 , 13 , 20 - 27 , 29 ] (near-infrared reflectance spectroscopy) in all included studies in this review, except in a single study [ 28 ] in which the FORE-SIGHT™ device (Edwards Lifesciences, USA) was used. All the studies reported baseline data with respect to rSO 2 including pre- and post-induction values, except for a single study [ 24 ] in which only the mean (SD) maximum fall of cerebral saturation values was reported.…”
Section: Resultsmentioning
confidence: 99%
“…To simplify, we classified the included heterogeneous studies based on whether the study authors used pharmacological (PPMs) or non-pharmacological prophylactic measures (NPPMs). For the prevention of MAP-dependent cerebral desaturations, PPMs were used in four RCTs (vasoactive agents; vasopressin [ 20 , 21 , 25 ], n = 3 and phenylephrine [ 7 ], n = 1) and NPPMs in eight (preloading with colloid [HES 130/0.4 [ 22 ], n = 1]; SCD use on legs [ 26 ], n = 1; compression stockings [ 13 , 24 ], n = 2; targeted mild hypercarbia [ 27 , 28 ], n = 2; or reduced BCP angle for surgery [ 23 ] [low BCP angle, ≤ 60º, n = 1] or RIPC [ 29 ], n = 1]). However, overlapping prophylactic measures were observed among the study groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Permissive HC was induced to 45 mmHg PaCO 2 in patients undergoing surgery in a reclined seated position which commonly results in an impaired haemodynamic stability at baseline. The results of this study demonstrated that mild HC prevented the reduction of cerebral oxygen saturation without changes in oxygenation index and haemodynamic parameters [ 96 ].…”
Section: Effects On the Cardiovascular Systemmentioning
confidence: 99%